MicroRNA-615-5p Regulates Angiogenesis and Tissue Repair by Targeting AKT/eNOS (Protein Kinase B/Endothelial Nitric Oxide Synthase) Signaling in Endothelial Cells - Icli, Basak; Wu, Winona; Ozdemir, Denizhan; Li, Hao; Cheng, Henry S.; Haemmig, Stefan; Liu, Xin; Giatsidis, Giorgio; Avci, Seyma Nazli; Lee, Nathan; Guimaraes, Raphael Boesch; Manica, Andre; et al. (Arteriosclerosis, thrombosis, and vascular biology, 2019)
OBJECTIVE—In response to tissue injury, the appropriate progression of events in angiogenesis is controlled by a careful balance between pro and antiangiogenic factors. We aimed to identify and characterize microRNAs that regulate angiogenesis in response to tissue injury. APPROACH AND RESULTS—We show that in response to tissue injury, microRNA-615-5p (miR-615-5p) is rapidly induced and serves as an antiangiogenic microRNA by targeting endothelial cell VEGF (vascular endothelial growth factor)-AKT (protein kinase B)/eNOS (endothelial nitric oxide synthase) signaling in vitro and in vivo. MiR-615-5p expression is increased in wounds of diabetic db/db mice, in plasma of human subjects with acute coronary syndromes, and in plasma and skin of human subjects with diabetes mellitus. Ectopic expression of miR-615-5p markedly inhibited endothelial cell proliferation, migration, network tube formation in Matrigel, and the release of nitric oxide, whereas miR-615-5p neutralization had the opposite effects. Mechanistic studies using transcriptomic profiling, bioinformatics, 3′ untranslated region reporter and microribonucleoprotein immunoprecipitation assays, and small interfering RNA dependency studies demonstrate that miR-615-5p inhibits the VEGF-AKT/eNOS signaling pathway in endothelial cells by targeting IGF2 (insulin-like growth factor 2) and RASSF2 (Ras-associating domain family member 2). Local delivery of miR-615-5p inhibitors, markedly increased angiogenesis, granulation tissue thickness, and wound closure rates in db/db mice, whereas miR-615-5p mimics impaired these effects. Systemic miR-615-5p neutralization improved skeletal muscle perfusion and angiogenesis after hindlimb ischemia in db/db mice. Finally, modulation of miR-615-5p expression dynamically regulated VEGF-induced AKT signaling and angiogenesis in human skin organoids as a model of tissue injury. CONCLUSIONS—These findings establish miR-615-5p as an inhibitor of VEGF-AKT/eNOS–mediated endothelial cell angiogenic responses and that manipulating miR-615-5p expression could provide a new target for angiogenic therapy in response to tissue injury.